IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TAI (TEAM ASISTENDINDIVIDUALIZATIONS) DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA TEMA PERTUMBUHAN DAN PERKEMBANGAN MAHLUK HIDUP DI KELAS III MI NW TUMPANG SARI - Rohiyatur Riadah (Al-mujahidah, 2022)
Abstract: The low student learning out comes because teachers are less varied in applying learning models, and there are often less effective learning methods, so that the result thing value does’nt incluede the KKN (minimum completeness criteria) value that has been determined. To improve the quality of student learning, learning does’nt only us the lecture model in the teaching and learning process but also needs to apply the model other learning models such as cooperative learning model TAI (Team Assistand Individualization). This research is a class room action research (CAR). Class room action research a consists of several cycles, but the researchers here use only cycle II, because the subject in this study where all third grade student, totalling 37 students. The instruments as in used in collecting data are observation sheets and tests that have passed the validation stage of 2 falidators. The results showed that the applycation of the cooperative leraning model tipe TAI (Team Assistand Individualization) can improve student cycle II, where the first cycle was 43% to 100% in the second cycle